Teacher Training Evolution in Ballet Education from Traditional Masters - Dubois, Catherine (International Journal of Humanities and Social Science, 2025)
The evolution of teacher training in ballet education has undergone significant transformation from the traditional master-apprentice model to contemporary pedagogical approaches that integrate technology, scientific understanding, and diverse methodological frameworks. This paper examines the historical progression of ballet teacher training, analyzing the transition from classical masters who dominated the field through personal expertise and lineage to modern approaches that emphasize systematic pedagogy, neuromuscular understanding, and digital empowerment. The study explores how traditional methods established foundational principles that continue to influence contemporary training while examining how modern innovations in dance science, technology-enhanced pedagogy, and collaborative learning environments have reshaped the landscape of ballet education. Through comprehensive analysis of training methodologies, pedagogical frameworks, and technological integration, this research demonstrates that while traditional master-based training provided essential artistic and technical foundations, contemporary approaches offer more inclusive, scientifically-informed, and accessible pathways for developing ballet educators. The findings reveal that successful modern ballet teacher training programs synthesize traditional artistic wisdom with evidence-based pedagogical practices, creating hybrid models that preserve the essence of classical ballet while addressing contemporary educational needs and diverse learning styles.